ANALYSIS OF SYARIAH OPERATIONAL FINANCIAL COURSE LEARNING ELEMENTS TO STUDENT FRUITFULNESS - Siti Aminah Anwar; Junaidi Junaidi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2017)
Learning Elements which consists of Internships, Practicum Books, Student Activity, and Mid-Final Exam can drive the level of success of students in taking the Syariah Financial Operations Course. The fact that there are 70% Students who have less satisfactory score in Syari'ah Financial Operations Course need to be explained. Therefore it is necessary to analyze which elements that can help and encourage the success level of students. The purpose of this study is (1) to justify the learning model of the Syariah Operational Financial Course (2) to analyze the factors affecting the success rate of Students (3) to detect the constraints that faced by the learning model element of the Syariah Operational Finance Course as well as offer solutions in minimizing problematics. The population of this study is students who have taken the Syari'ah Financial Operations Courses (150-190 students or 90-95% of the population). In collecting data, researcher uses interview and questionary. Researcher uses qualitative descriptive approach to answer the objectives (1) and (3). While the others research objective is answered through Multiple Regression. Prominent analysis results can be used as a basis in revising future learning models.Keywords: Internships, Practicum Books, Student Activity, Mid-Final Exam, Student Result